Trabalho escravo urbano na construção civil: condições degradantes e a experiência do operariado vinculado ao sindicato dos trabalhadores da indústria da construção civil e em frentes de obras em Belém do Pará - MARTINS, Omar Conde Aleixo (Universidade Federal do Pará, 2018)
This work is situated in the context of legal discussion about the labor analogous to slavery in its urban occurrence, bringing to debate the issue of forced labor in civil construction, specifically by one of the crime execution modes, namely the degrading conditions work. Thus, the main objective of the research was to investigate to what extent the social and legal reality of work of construction workers in Belém/PA, from the very perception of these about their social rights, appears as forced labor urban under the focus of degrading conditions. Was used to achieve the proposed objective, the literature search in books, periodicals and journals, as well as a case study concerning forced labor in civil construction, recognized judicially, in the city of Americana/SP; finally, closing the methodological framework, we used the field research through interviews structured and interviews by guidelines with members of state institutions devoted to combat slave labor, and, especially, with civil construction workers to work fronts in Belém/PA and the head office of the Labor Union category, in the same city. The work is divided into three chapters and begins with a visit to the sociological understanding around the city and its impacts in urban labor relations, succeeding a discussion about the slave labor in Brazil and its theoretical and normative pillars, both those from the international standards, as those derived from art. 149 of the Penal Code, which defines the delict device to reduce others to work analogous to slavery, ending with reflections on the essentially urban manifestation of the delict under investigation. Secondly, again moves by the sociological universe to capture some capitalist components of contemporary industry, in addition to the implications arising from the social profile of the slave worker and the typical civil construction worker; closes the chapter with an analysis on the legal concept of degrading conditions and the case study that once announced on forced labor in civil construction. Finally, in the third chapter, we present the field research carried out and the reflections and conclusions drawn from the research as well as a discussion of coping policies to modern-day slavery, their effectiveness and what may be proposed from the crime of study in its urban occurrence, more precisely, in civil construction. The research found that, even if the working conditions of workers interviewed did not characterize submission to degrading conditions, several peculiarities of the service in civil construction need to be considered in assessing, or not, of degrading work, as they may represent aspects of social rights violations and, depending on the case, affront to decent work and the dignity of the human person, grounds protected by the seal to undergo a human being to degrading working conditions.